Do female commissioners have higher social responsibility? Research in manufacturing companies in Indonesia - Fahmi, Nuria; Adhivina, Vitta (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2019)
This study aims to test the slack resources and feminism of the board on the quality of corporate social responsibility disclosure. The population of this study is all companies listed on the Indonesian Stock Exchange during the 2014-2016 period. The data are collected by using the official IDX website. From this research, there were 539 companies listed in 2016, 525 companies listed in 2015 and 498 companies listed in 2014. This research consists of 75 companies that published a sustainability report. The purposive sampling technique used for selecting the sample. The results of this study found that the slack resources and the feminism of the director has no significant effect on the quality of CSR disclosure while the feminism of commissioners has a negative impact on the quality of CSR disclosure.